Objective Factors Determining the Development of Online Self-study Skills During the Global COVID-19 Pandemic - from The Perspective of Students’ Experiences - Joanna KRZYŻAK; Jolanta WALAS-TRĘBACZ (Communications of International Proceedings, 2021)
The publication includes a theoretical part that describes in a synthetic way selected objective factors determining the development of self-study skills in the online environment, and a practical part, which focuses on the analysis of the results of a survey conducted among students of Cracow’s universities. The study was conducted using a compiled questionnaire after the first year of crisis education at the end of the summer semester of the 2020/2021 academic year. The survey form was sent to the respondents using the CAWI (computerassisted web interview) technique using the Google Forms application. In the study participated 825 people. The respondents voluntarily and anonymously expressed their opinion on: advantages, disadvantages, study conditions, threats and expectations related to the remote study process of study during the pandemic and after its end. The statistical analysis of the collected results was performed with the use of the Statistica PL 13.3 package. The purpose of this study is therefore an attempt to determine whether, in the opinion of the surveyed students, remote study during crisis education was conducive to the development of their self-learning skills, from the point of view of objective factors. In addition, the study presents conclusions and discussions for the further improvement the process of self-education in the online environment.
Keywords: students; self-education skills; distance learning; COVID-19